2016
DOI: 10.18172/cig.2931
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the frequency and severity of hydrological droughts over Ethiopia from 1960 to 2013

Abstract: ABSTRACT. Here we present an analysis of drought occurrence and variability in Ethiopia, based on the monthly precipitation data from the Climate Research Unit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 65 publications
(87 reference statements)
6
25
0
Order By: Relevance
“…This was also true all over Ethiopia. This finding agrees with previous research findings of (El Kenawy et al, 2016;Mosaad, 2015;Bayissa et al, 2015;Degefu and Bewket, 2013;Viste et al, 2012;Tagel et al, 2011;Edossa et al, 2010;Bewket and Conway, 2007) who reported extreme drought in different parts of the country in the same period. Segele and Lamb (2005) also extensively demonstrated the severity of the 1984 drought over Ethiopia, particularly during the summer season.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was also true all over Ethiopia. This finding agrees with previous research findings of (El Kenawy et al, 2016;Mosaad, 2015;Bayissa et al, 2015;Degefu and Bewket, 2013;Viste et al, 2012;Tagel et al, 2011;Edossa et al, 2010;Bewket and Conway, 2007) who reported extreme drought in different parts of the country in the same period. Segele and Lamb (2005) also extensively demonstrated the severity of the 1984 drought over Ethiopia, particularly during the summer season.…”
Section: Discussionsupporting
confidence: 93%
“…The analysis implies that drought magnitude can vary largely over space and this exceptional extreme drought shows a local character, where small area was affected, while others had less severe drought magnitude or even no drought. This finding is supported by the study of El Kenawy et al (2016) who found similar drought occurrences in studying the changes in the frequency and severity of hydrological droughts over Ethiopia from 1960 to 2013.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Erosion and sedimentation are challenging problems that are increasingly difficult to solve with the intensification of land use (Cerdà, Imeson, & Poesen, ; Erkossa, Wudneh, Desalegn, & Taye, ). In the Ethiopian highlands with rapid population growth, sediment concentrations have been increasing (Gebremicael, Mohamed, Betrie, van der Zaag, & Teferi, ; Mekonnen, Keesstra, Baartman, Ritsema, & Melesse, ; Steenhuis et al, ; Tesemma, Mohamed, & Steenhuis, ) without a significant precipitation increase in the past 40 years (Conway, ; El Kenawy et al, ; Kim & Kaluarachchi, ; Nyssen et al, ; Seleshi & Demaree, ; Tekleab, Mohamed, & Uhlenbrook, ; Tesemma et al, ). Measures are being taken to reduce erosion but only in a few cases have they been checked for their effectiveness (Dagnew et al, ; Mekonnen et al, ; Walling, ; Walter, Steenhuis, & Haith, ).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the effectiveness of landscape modifications is especially timely in the Ethiopian highlands where, in an attempt to increase prosperity and assure food security for the rapidly increasing population in the context of recurring drought (El Kenawy et al, ; Hurni, , ; Nyssen et al, ), the Ethiopian government is implementing management practices for increased rainwater productivity and increased life spans for hydroelectric power plants such as the Grand Ethiopian Renaissance Dam on the Blue Nile near Sudan (Chen & Swain, ; Dagnew et al, ; Humphreys et al, ; Mekonnen et al, ; MOA, ; MOFED, ). Defining the relationship between modifications in the landscape and resulting changes in hydrology (including runoff, sediment concentrations, and sediment load) has become possible in recent decades due to the efforts of various research programs in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%